Hindu religious practices exposed in Malaysian Tamil movies - SillIalee, K.; Rajantheran, R. (2014)

(untitled)
Late 19th and ear1y 20th centuries marks the mass migration of people from India to Malaya to work in estates while minority of them came as merchants and to work in civil service. The majority group started their religious practice by worshiping the demigods. On the other hand, the minority group settled in urban areas and they initiated the proper religious practice by building temples for the main deities such as Lord Siva, Lord Muruga as well as Lord Vishnu. After the independence of Malaya, many of those residing in the estates began to shift to urban areas for improvements in their life. These people began to have realisation on the actual way of religious practice and were attracted to the prayers to the main deities such as Lord Shiva and Lord Muruga. Currently, besides the prayers to the main deities, Malaysian Indians have high level or spiritual awareness such as meditation and Siddha philosophy. Though there is a significant evidence or religious awareness among Malaysian Indians, Tamil movies produced in Malaysia still centres in the olden religious practice and the worship to demigods. As such, this research intends to explore the reason for the production of such themes in local Tamil movies. Besides, the researcher also wants to find out the reality in comparison to the movie projections. This research also would shed light the movie of the local Tamil movie producer in exposing the olden religious practice rather than the reality.